Peer Privacy Concern: Conceptualization and Measurement - Zhang, Nan (Andy); Wang, Chong (Alex); Karahanna, Elena; Xu, Yan (MIS Quarterly, 2022)
Privacy needs on today’s internet differ from the information privacy needs in traditional e-commerce settings due to their focus on interactions among online peers rather than merely transactions with an online vendor. Peer-oriented online interactions have critical implications for an individual’s virtual presence and self-cognition. Yet existing conceptualizations of internet privacy concerns have solely focused on the control of personal information release and on online interactions with online vendors. Drawing on the theory of personal boundaries, this study revisits the theoretical foundation of online privacy and proposes a multidimensional peer-related privacy concern construct, that focuses on privacy violations from online peers. We term this new construct “Peer Privacy Concern” (PrPC) and define it as the general feeling of being unable to maintain functional personal boundaries in online activities as a result of the behavior of online peers. This construct consists of four dimensions comprised of a reconceptualization of information privacy concerns to also reflect privacy concerns with respect to peers’ handling of self-shared information and with respect to peer-shared information about one’s self, and three new dimensions that tap into the arising privacy needs from virtual interactions (i.e., virtual territory privacy concern and communication privacy concern) as well as from the need to maintain psychological independence (i.e., psychological privacy concern). These new dimensions, which are rooted in the theory of personal boundaries, are prominent privacy needs in online social interactions with peers. However, they are absent from previous privacy concern conceptualizations. Scales for measuring this new construct are developed and empirically validated.